International cooperation and the internationalization of small to medium-sized entreprises in Medellín: A case-comparison study [Cooperação internacional na internacionalização de pequenas e médias empresas de Medellín: Um estudo de caso comparado] [La cooperación internacional en la internacionalización de pequeñas y medianas empresas de Medellín: Un estudio de caso comparado] (2014)
The aim of this article is to describe the contribution of international cooperation programs in the internationalization of small and medium enterprises in Medellin. Qualitative methodology is developed through multiple case studies of four companies that participated in international cooperation programs. The enterprises are evaluated in their internationalization process using the Uppsala model. The results show that the programs only contributes to the initial stage of the internationalization process. The conclusion shows that internationalization will depend on the way companies make use of their knowledge and develop a good experimental model for building trust and trading networks. © 2013 Universidad ICESI. Published by Elsevier España, S.L. All rights reserved.